2011
DOI: 10.1007/s00264-011-1394-4
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of the anatomical basis of fracture for the subsequent treatment of the anterior humeral circumflex artery and the axillary nerve

Abstract: Purpose The purpose of this study was to determine the location of the anterior humeral circumflex artery and axillary nerve based on bony landmarks, and to provide anatomical information that enables a safe approach when treating a proximal humeral fractures. Methods Thirty cadavers were included. The distances of both the anterior humeral circumflex artery and the axillary nerve from body landmarks were measured using Vernier calipers. Results The mean distance between the inferior border of the medial acrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The average greater tuberosity distances reported by Chen et al and Gardner et al were within 1 mm of our findings along with their reported average trans-humeral ANVB angles which both within 2.5 degrees of our measurements. 8 , 15 Finally, comparing our inferior articular margin measurement to the only literature report by Bono et al, we reported the average distance being about 4 mm less with a much smaller range and standard deviation. These findings support the assessment of ANVB positioning using advanced imaging.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The average greater tuberosity distances reported by Chen et al and Gardner et al were within 1 mm of our findings along with their reported average trans-humeral ANVB angles which both within 2.5 degrees of our measurements. 8 , 15 Finally, comparing our inferior articular margin measurement to the only literature report by Bono et al, we reported the average distance being about 4 mm less with a much smaller range and standard deviation. These findings support the assessment of ANVB positioning using advanced imaging.…”
Section: Discussionsupporting
confidence: 69%
“… 35 , 40 EMG identified axillary nerve injuries have been as high as 42% with the deltopectoral approach and 33% with the deltoid splitting approach. 8 A systematic review identified a 3% injury with a deltopectoral approach and a 7% injury the anterolateral deltoid splitting approach. 53 These studies are limited by low numbers and the need for electrophysiologic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCHA was considered classic if it arose from the third part of the axillary artery and traveled posteriorly around the proximal humerus. The ACHA was defined as classic if it arose from the third part of the axillary artery and followed a horizontal course to the bicipital groove [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The AHCA branches off the axillary artery at the lower border of the subscapularis and follows a horizontal course behind the coracobrachialis muscle to the bicipital groove approximately 5 cm below the inferior border of the acromion. 21 The ascending branch (arcuate artery) of the AHCA ascends on the lateral border of bicipital groove and enters the proximal humerus at the level of the greater tuberosity. 22 The greatest risk to the axillary nerve occurs during the initial dissection after the two heads of the deltoid muscle have been split.…”
Section: The Humerus Proximal Humerus Fracturementioning
confidence: 99%